PENGARUH FAKTOR HARGA, KUALITAS, DAN FITUR TERHADAP KEPUTUSAN PEMBELIAN MODEM SMARTFREN DI KETINTANG SURABAYA - KHOLISHOTUN N, ENNIK (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Telecommunications increasingly tight competition marked by the mushrooming number of internet service provider (ISP) in Indonesia. In a tight competition, the main purpose of the company retain customers or get a loyal customer with a product or service they use for the company to survive and win the competition.One way for companies to gain loyal customers is by creating quality products, products that match the tastes, desires and needs of consumers. At least know the benefits of the product, consumers will see product based on attributes or characteristics of the product. Modem Smartfren an Internet Service Provider (ISP) that has good quality, comprehensive features and low price and in accordance with the benefits and facilities available consumer. From this research, using multiple linear regression, it is known that there is a direct relationship between the variable X is an attribute of products which consist of price, quality, and features, with the purchase decision variable Y. Product attributes including price, quality and features sihnifikan jointly influence consumers' purchasing decisions. Most consumer purchase decisions are influenced by the price of quality and features. Price factor (X1) becomes the most dominandalam factors affecting consumer decisions modem smartfren. Keywords : factor price of quality and features, purchasing decisions